On Optimizing H. 264/AVC Rate Control by Improving R-D Model and Incorporating HVS Characteristics. (29th August 2010) - Zhu, Zhongjie; Wang, Yuer; Bai, Yongqiang; Jiang, Gangyi
Abstract : The state-of-the-art JVT-G012 rate control algorithm of H.264 is improved from two aspects. First, the quadratic rate-distortion (R-D) model is modified based on both empirical observations and theoretical analysis. Second, based on the existing physiological and psychological research findings of human vision, the rate control algorithm is optimized by incorporating the main characteristics of the human visual system (HVS) such as contrast sensitivity, multichannel theory, and masking effect. Experiments are conducted, and experimental results show that the improved algorithm can simultaneously enhance the overall subjective visual quality and improve the rate control precision effectively.